Private Property and Social Capital: Dynamics of Exclusion and Sharing in the Subdivided Pastoral Rangelands of Kajiado, Kenya. Issue 1 (2nd January 2022) - Jeppesen, Maja Dahl; Hassan, Rahma
Abstract: Pastoral livelihoods are presented with new challenges as access to land is altered by climate change and privatization. Pastoralist livelihoods however continue to be reliant on mobility and pastoralists, therefore, continue to negotiate access to land in the privatized and subdivided rangelands. Various dynamics enable and constrain pastoralists' access under this new form of land tenure, but little work has investigated the underlying power structures of access and the importance of private property for this. Based on field work in the subdivided rangelands of Kajiado county in Kenya, we argue that social structures and formal land ownership both enable and hinder pastoralists' access to land. Moreover, while social capital is one of the most important factors for accessing pastures in subdivided rangelands, private property rights have an overarching importance for relations of access. As a result, the group ranches' uneven allocation of land to its members has deepened inequalities in the community.